2015
DOI: 10.2220/biomedres.36.357
|View full text |Cite
|
Sign up to set email alerts
|

<b>α1-Adrenoceptors relate Ca</b><sup><b>2+</b></sup><b> modulation and protein secretions in rat lacrimal </b><b>gland </b>

Abstract: Noradrenaline (NA) is a catecholamine with multiple roles including as a hormone and a neurotransmitter. Cellular secretory activities are enhanced by adrenergic stimuli as well as by cholinergic stimuli. The present study aimed to determine which adrenoceptors play a role in controlling intracellular calcium ion ([Ca 2+ ] i ) level in acinar cells of rat lacrimal glands. Expression of mRNA for adrenoceptor subtypes in the acinar cells was assessed using RT-PCR. ] i increase. The peroxidase activity was q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…As another possible mechanism, alteration of metabolism at the lacrimal gland cellular level through the α 2 -adrenoceptor has been proposed to decrease tear production [32]. At present, although the existence or function of α 1 -adrenoceptor in the lacrimal gland in rats or mice has been reported, there have been no reports regarding the α 2 -adrenoceptor in the lacrimal glands of any species [55,56]. Furthermore, it was also suggested that increased antinociception modulated by α 2 -adrenoceptor decreases reflex tear secretion [32].…”
Section: Discussionmentioning
confidence: 99%
“…As another possible mechanism, alteration of metabolism at the lacrimal gland cellular level through the α 2 -adrenoceptor has been proposed to decrease tear production [32]. At present, although the existence or function of α 1 -adrenoceptor in the lacrimal gland in rats or mice has been reported, there have been no reports regarding the α 2 -adrenoceptor in the lacrimal glands of any species [55,56]. Furthermore, it was also suggested that increased antinociception modulated by α 2 -adrenoceptor decreases reflex tear secretion [32].…”
Section: Discussionmentioning
confidence: 99%
“…Because α-adrenergic stimulation is generally linked to Ca 2+ signaling, the effect of phenylephrine on [Ca 2+ ] i and ductal fluid secretion was investigated. 23 Although phenylephrine stimulation resulted in a small but statistically significant elevation of [Ca 2+ ] i , no statistically significant difference could be demonstrated in the fluid secretion between the Ca 2+ -chelator BAPTA-AMtreated and nontreated ducts.…”
Section: Discussionmentioning
confidence: 87%
“…However, in the present study, isoproterenol failed to induce an increase in [Ca 2+ ] i in cerebral arteriole smooth muscle cells (data not shown). We previously reported that isoproterenol failed to induce an increase in [Ca 2+ ] i in lacrimal gland acinar cells, whereas noradrenaline mainly stimulated α1-adrenoceptors that induced an increase in [Ca 2+ ] i , which subsequently stimulated protein secretion in these cells (Satoh et al 1997;Ikeda-Kurosawa et al 2015).…”
Section: Discussionmentioning
confidence: 98%